Inhibition of interferon gamma impairs induction of experimental epidermolysis bullosa acquisita - Gross, Natalie; Marketon, Jana; Mousavi, Sadegh; Kalies, Kathrin; Ludwig, Ralf J.; Bieber, Katja (Frontiers in Immunology, 2024)
Epidermolysis bullosa acquisita (EBA) is a muco-cutaneous autoimmune disease characterized and caused by autoantibodies targeting type VII collagen (COL7). Treatment of EBA is notoriously difficult, with a median time to remission of 9 months. In preclinical EBA models, we previously discovered that depletion of regulatory T cells (Treg) enhances autoantibody-induced, neutrophil-mediated inflammation and blistering. Increased EBA severity in Treg-depleted mice was accompanied by an increased cutaneous expression of interferon gamma (IFN-y). The functional relevance of IFN- in EBA pathogenesis had been unknown. Given that emapalumab, an anti-IFN-y antibody, is approved for primary hemophagocytic lymphohistiocytosis patients, we sought to assess the therapeutic potential of IFN-y inhibition in EBA. Specifically, we evaluated if IFN-y inhibition has modulatory effects on skin inflammation in a pre-clinical EBA model, based on the transfer of COL7 antibodies into mice. Compared to isotype control antibody, anti-IFN-y treatment significantly reduced clinical disease manifestation in experimental EBA. Clinical improvement was associated with a reduced dermal infiltrate, especially Ly6G+ neutrophils. On the molecular level, we noted few changes. Apart from reduced CXCL1 serum concentrations, that has been demonstrated to promote skin inflammation in EBA, the expression of cytokines was unaltered in serum and skin following IFN-y blockade. This validates IFN-y as a potential therapeutic target in EBA, and possibly other diseases with a similar pathogenesis, such as bullous pemphigoid and mucous membrane pemphigoid.